Marges de la philosophie - Derrida, Jacques 1930-2004 (Paris Éditions de Minuit, 1972)
in Margins of Philosophy Jacques Derrida constitutes the key to an understanding of deconstructionism and the philosophy of differentiation. In this book, Derrida emphasizes the problematic, self-undermining nature of truth claims in the philosophical tradition, from Plato, Kant, Hegel and Nietzsche to the phenomenology of Husserl and Heidegger and analytic-philosophical language theory.
Includes bibliographical references.
Keywords: Philosophy; Linguistics